Penyalahgunaan Wewenang oleh Kepala Desa dalam Tindak Pidana Korupsi APBDesa Studi Putusan Nomor: 21/Pid.Sus.TPK/2022/PT.Pbr - Wandi; Juniarti (Jurnal Indragiri Penelitian Multidisiplin, 2025)
The consideration of the panel of judges in Decision Number: 21/Pid.Sus.TPK/ 2022/PT.Pbr was correct where the defendant's actions were Abuse of Authority attached to the Defendant for the opportunities and means available to him because of the Defendant's position as Pelanduk Village Head based on the Decree of the Regent of Indragiri Hilir Number: Kpts. 7151/X/HK-2017 dated October 11, 2017 as in the Subsidiary Indictment of the Public Prosecutor.Abuse of authority based on the three terms above have the same meaning that both explain the deviations that occur as a result of abuse of authority. The substance to be explained is the same but the way it is applied is different, whether it is seen from deviations due to contradictions in the rules either regulated in the Act, the exercise of authority of other officials or exceeding what is appropriate with the provisions.